Increased EGFR Phosphorylation Correlates with Higher Programmed Death Ligand-1 Expression: Analysis of TKI-Resistant Lung Cancer Cell Lines. (8th October 2017) - Suda, Kenichi; Rozeboom, Leslie; Furugaki, Koh; Yu, Hui; Melnick, Mary Ann C.; Ellison, Kim; Rivard, Christopher J.; Politi, Katerina; Mitsudomi, Tetsuya; Hirsch, Fred R.
Abstract : Despite the recent development of immunotherapies that target programmed death-1 (PD-1) or programmed death ligand-1 (PD-L1) in non-small cell lung cancer (NSCLC) treatment, these therapies are less effective in NSCLC patients with epidermal growth factor receptor (EGFR) mutations. However, the molecular mechanisms underlying this lower efficacy of immunotherapies in EGFR mutant lung cancers are still unclear. In this study, we analyzed PD-L1 protein expression in lung cancer cell lines with EGFR mutations prior to and after acquisition of resistance to EGFR tyrosine kinase inhibitors (TKIs). We found that parental lung cancer cell lines harboring EGFR mutations showed negative (PC9 and H3255 cells) and positive (HCC827 cells) staining for PD-L1 by immunohistochemistry. Comparing PD-L1 expression between EGFR-TKI resistant cell lines and their parental cells, we found that increased phosphorylation of EGFR was related to increased expression of PD-L1. Increased phosphorylation of EGFR was accompanied by the T790M secondary mutation. Acquired resistance cells with MET amplification or EGFR loss both showed decreased phosphorylation of EGFR and decreased PD-L1 expression. Our results indicate that lung cancer cell lines with EGFR mutations (parental cells) do not harbor high PD-L1 protein expression. In addition, EGFR phosphorylation affects PD-L1 expression after acquisition of resistance to EGFR-TKIs.